New host plant records of Humerobates rostrolamellatus Grandjean in Italy - De Giosa, Marcello (2022)
Humerobates rostrolamellatus Grandjean is an oribatid mite species commonly found in association with fruit trees like apple trees and plums. We sampled twigs and leaves of 12 different trees in the Apulia territories in Southern Italy in 2019. Here we report 11 new host plant records for H. rostrolamellatus; no damage has been observed on the trees associated with the mite populations.